Assessment tools and strategies used by Jamaican secondary school teachers - Clavia Williams-mcbean (International Journal of Assessment Tools in Education)
There is an increasing understanding that assessment is an integral part of teaching and learning and that teachers are largely not adequately prepared for their assessment responsibilities. Consequently, there is a need for research on what teachers need to improve their assessment practices. To determine what Jamaican secondary school teachers need, this mixed methods study was conducted to describe the assessment tools and strategies used by secondary school teachers of various subjects and in different types of schools as the basis for future interventions. Data was collected from a survey of 1088 secondary school teachers of varying subjects and school types and further explored through interviews and observations of 32 teachers of English. Analysis of the data using descriptive statistics and ANOVA in the quantitative phase revealed that secondary school teachers primarily used traditional assessment tools and strategies, particularly tests, despite school type. Pattern coding and pattern matching in the qualitative phase confirmed these results. The findings also revealed statistically significant differences in the frequency of use of traditional and alternative assessment tools and strategies based on the subject the teachers taught. Qualitative explorations revealed that school policies that require a quota of grades and state or express positive attitudes towards tests influenced teachers despite school type to use traditional methods. The findings imply that school administrators need to implement supportive school-level policies and display positive attitudes toward alternative assessments to maximize the use of assessment to improve learning.